KATA-KATA TABU DALAM BAHASA INGGRIS DAN BAHASA MONGONDOW (SUATU ANALISIS KONTRASTIF) - PAPUTUNGAN, RIESKA ELANDA; KODONG, FENTJE; PAMANTUNG, RINA P. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2019)
ABSTRACTThis research is entitled â€œTaboo Words in English and Mongondow Language: A Contrastive Analysisâ€ is analyzed and describe in sociolinguistic field. The objectives of this research are to identify, classify and describe the types and meaning of taboo words and to analyze their differences and similarities in English and Mongondow Language. This research used a descriptive method. The data is analyzed using theory of Wardhaugh (1986:230) to find out the types, using Leechâ€™s theory (1981:19) to find out the meaning, and were contrasted to find out the differences using Ladoâ€™s theory (1971:217). The significances of this research are theoretically, this research is expected to give contribution to the development of sociolinguistics especially in terms of taboo words and to practically, this research can be useful, for young Mongondow generation who want to learn taboo words in English and for foreign learners who want to study taboo words in Mongondow language. The result of this research shows that taboo words found in Mongondow language were classified into eight types, they are, sex, excretion, bodily function, death, animal, religion, supernatural and hollo. The simillaritiess in English and Mongondow Language is the use of this word can cause misunderstanding and the differences of English and Mongondow Language is taboo words in Mongondow have levels whereas in English there is no level. This shows that the causes of using taboo words are to express the happiness, such as anger, emotion, and surprise, to joke, to insult, and to talk about sex.Â Keywords : Taboo Words; English and Mongondow Language; Contrastive Analysis.